Discussion Note: Complexity-Aware Monitoring (USAID, 2018)
This Discussion Note complements ADS 201 and outlines general principl es and promising approaches for monitoring complex aspects of USAID de velopment assistance. Complexity-aware monitoring is a type of complem entary monitoring that is useful when results are difficult to predict due to dynamic contexts or unclear cause and-effect relationships. Ke y principles of the Program Cycle include applying analytic rigor, man aging adaptively, and utilizing a range of approaches to achieve resul ts. ADS 201.3.5.5 identifies three types of program monitoring – perfo rmance, context, and complementary. All USAID programming incorporates performance monitoring and should include context monitoring. Perform ance monitoring “is the ongoing and systematic collection of performan ce indicator data and other quantitative or qualitative information to reveal whether implementation is on track and whether expected result s are being achieved.” Context monitoring is “[t]he systematic collect ion of information about conditions and external factors relevant to t he implementation and performance of an operating units (OU’s) strateg y, projects, and activities.” As stated in ADS 201.3.5.5, complementar y monitoring may be used by missions and Washington OUs to complement performance and context monitoring in situations where results are dif ficult to predict due to dynamic contexts or unclear cause-andeffect r elationships. This Discussion Note provides an explanation of when to use complementary monitoring approaches that are complexity-aware and summarizes the three principles of complexity-aware monitoring.